Arterial haemodynamics and coronary artery calcification in adult patients with juvenile idiopathic arthritis. Issue 8 (2nd April 2014) - Aulie, Hanne A; Selvaag, Anne M; Günther, Anne; Lilleby, Vibke; Molberg, Øyvind; Hartmann, Anders; Holdaas, Hallvard; Flatø, Berit
Abstract : Objective: To compare arterial haemodynamics in adults with long-term juvenile idiopathic arthritis (JIA) to that of healthy controls, and explore the influence of traditional cardiovascular risk factors and disease characteristics on arterial haemodynamics plus coronary artery calcification. Methods: 87 JIA patients (median age 38.4 years) with persistently active disease at least 15 years after disease onset (registered by longitudinal follow-up), were re-examined after median 29 years and compared with 87 matched controls. Arterial haemodynamics were characterised by arterial stiffness and blood pressure. Sphygmocor was used to measure the arterial stiffness markers pulse wave velocity (PWV) and augmentation index (AIx). Coronary calcification was assessed by CT. Results: Compared to controls, patients had significantly higher PWV (7.2 vs 6.9 m/s, p=0.035), and systolic and diastolic blood pressure (SBP, p=0.050 and DBP, p=0.029). AIx was numerically higher in the patients compared to the controls, but no statistically significant difference was found. Coronary calcification was present in 22 (26%) of the patients. Daily smoking was more frequent (p=0.043), and insulin resistance was higher (p=0.034) in patients than controls. In patients, DBP, but no disease variables were determinants of PWV. Disease variables as well as traditional cardiovascular risk factors were associated with higher AIx, DBP and the presence of coronary calcification. Conclusions: JIA patients with long-term active disease had altered arterial haemodynamics compared with controls in our study. PWV was mainly determined by increased DBP, a parameter that again was associated with JIA disease and treatment variables.